Artificial intelligence with Python : your complete guide to building intelligent apps using Python 3.x and TensorFlow 2 - Artasanchez, Alberto; Joshi, Prateek (Packt Publishing, 2020)
Completely updated and revised edition of the bestselling guide to artificial intelligence, updated to Python 3.8 and TensorFlow 2, with seven new chapters that cover RNNs, AI & Big Data, fundamental use cases, machine learning data pipelines, chatbots, Big Data, and more.